DO VAT INCREASES AND DIGITAL MARKETING AFFECT GEN Z PURCHASE DECISIONS? THE MODERATING EFFECT OF E-COMMERCE TRANSACTIONS - Nensi Yuniarti. Zs; Inda Tri Rahayu; Furqonti Ranidiah; Dinal Eka Pertiwi (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
In the digital era, consumer behavior—especially among Generation Z—has changed significantly due to easy access to information and online shopping. This generation is technologically literate, values experiences, is socially aware, and is influenced by peers and influencers. This study aims to analyze the effects of value-added tax (VAT) increases and digital marketing on Generation Z’s purchasing decisions, with e-commerce transactions serving as a moderating variable. The research employs a quantitative approach, collecting primary data  through an online questionnaire from 294 students of the Faculty of Economics and Business at Universitas Muhammadiyah Bengkulu. Participants were selected using the Slovin formula from a population of 1,108 students. Data were analyzed using SmartPLS 4. The results indicate that VAT increases have no significant effect on purchasing decisions (t = 1.816; p = 0.069), whereas digital marketing has a significant effect (t = 2.894; p = 0.004). Additionally, e-commerce transactions do not moderate the effects of VAT increases (t = 0.324; p = 0.746) or digital marketing (t = 0.858; p = 0.391) on purchasing decisions.